Multi-channel entanglement distribution using spatial multiplexing from four-wave mixing in atomic vapor. Issue 3 (4th February 2016) - Gupta, Prasoon; Horrom, Travis; Anderson, Brian E.; Glasser, Ryan; Lett, Paul D.
Abstract : Four-wave mixing in atomic vapor allows for the generation of multi-spatial-mode states of light containing many pairs of two-mode entangled vacuum beams. This in principle can be used to send independent secure keys to multiple parties simultaneously using a single light source. In our experiment, we demonstrate this spatial multiplexing of information by selecting three independent pairs of entangled modes and performing continuous-variable measurements to verify the correlations between entangled partners. In this way, we generate three independent pairs of correlated random bit streams that could be used as secure keys. We then demonstrate a classical four-party secret sharing scheme as an example for how this spatially multiplexed source could be used.